2017
DOI: 10.1039/c7ta05378a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the role of Lewis bases in the ripening process of perovskite films for highly efficient perovskite solar cells

Abstract: The ripening effect of Lewis bases on perovskite films is investigated and PSCs based on a synergistic DMSO/urea system exhibit a PCE of 20.06%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 31 publications
7
120
0
1
Order By: Relevance
“…Impressively, the GdF 3 –aminobutanol‐based device displays a PCE of 21.21% with open‐circuit voltage ( V OC ) of 1.17 V, short‐circuit current density ( J SC ) of 23.21 mA cm −2 and fill factor ( FF ) of 0.78. Huang et al revealed a correlation between V OC and grain boundaries, and we also attribute the increasing V OC in GdF 3 –aminobutanol‐based device to the reduction of grain boundaries . Likewise, the larger grain size could efficiently reduce grain boundaries which is beneficial for the suppression of charge carrier recombination, resulting in an increase of FF and J SC …”
supporting
confidence: 54%
“…Impressively, the GdF 3 –aminobutanol‐based device displays a PCE of 21.21% with open‐circuit voltage ( V OC ) of 1.17 V, short‐circuit current density ( J SC ) of 23.21 mA cm −2 and fill factor ( FF ) of 0.78. Huang et al revealed a correlation between V OC and grain boundaries, and we also attribute the increasing V OC in GdF 3 –aminobutanol‐based device to the reduction of grain boundaries . Likewise, the larger grain size could efficiently reduce grain boundaries which is beneficial for the suppression of charge carrier recombination, resulting in an increase of FF and J SC …”
supporting
confidence: 54%
“…32 Yang and coworkers rst used urea and thiourea as additives for CH 3 -NH 3 (MA)PbI 3 derived normal (ITO/TiO 2 ) PSCs, and demonstrated a PCE of 18.25% using an annealing temperature of 100 C. 10 Meng et al used DMSO/urea to increase the PCE of normal devices up to 20.06% with the perovskites (FAPbI 3 ) 0.75 (MAPbI 3 ) 0.17 (MAPbBr 3 ) 0.08 and urea derived antisolvent washing process. 33 Considering the complexity of perovskite compositions and the myriad fabricating parameters involved in the previous process, we explored the urea and thiourea as simple precursor additives for inverted (MAPbI 3Àx -Cl x and MAPbI 3 ) PSCs. We adopted the ITO/NiO x or PEDOT:PSS/ perovskite/PCBM/Ag structure and found the performance up to 18.8% with little hysteresis for urea-derived devices using a low annealing temperature, as low as 85 C. In particular, the grain size of perovskite can be grown up to 935 nm-which was as twice large as those using conventional method and became a key factor on contributing to the high PCE.…”
Section: +mentioning
confidence: 99%
“…[10] They argued that the Lewis acid-base interaction between the perovskite precursors and the urea might increase the critical Gibbs free energy of nucleation, which decreases the number of nuclei formed. [15] We believed that www.advmat.de www.advancedsciencenews.com urea and/or thiourea could be incorporated as core functional moieties in a newly designed semiconducting chemical additive to increase the size and homogeneity of perovskite grains. [15] We believed that www.advmat.de www.advancedsciencenews.com urea and/or thiourea could be incorporated as core functional moieties in a newly designed semiconducting chemical additive to increase the size and homogeneity of perovskite grains.…”
Section: Doi: 101002/adma201805554mentioning
confidence: 99%
“…This result indicates the existence of SA-1 within the perovskite film with a gradient distribution in the vertical direction in the perovskite layer. However, the details of the nucleation and growth mechanisms (i.e., the effect of the Lewis acid-base interaction on the nucleation and growth kinetics of perovskite crystals) remain unclear; [10,14,15] thus, we are currently performing further mechanistic investigations through combined experimental (e.g., 2D IR spectroscopy) and theoretical methods. The EDS mapping of each element confirmed that the entire device consisted of indium tin oxide (ITO)/hole transport layer (HTL)/perovskite with SA-1/PCBM/ZnO/Ag, respectively.…”
Section: Doi: 101002/adma201805554mentioning
confidence: 99%